Criteria for Selective Territorial Expansion: Case Study of the Republic of Kazakhstan - SHUMAKOVA, Oksana Viktorovna; BAETOVA, Dinar Rahmetulovna; DMITRENKO, Elena Aleksandrovna; NOVIKOV, Yuriy Ivanovich; BLINOV, Oleg Anatolievich (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
This paper assesses the development of the regions of the Republic of Kazakhstan from the perspective of selective territorial expansion of a company specializing in the manufacture of metal structures. The notion of selective territorial expansion of companies as a corporate development strategy is considered, including its place in the taxonomy of organizational strategies. The paper substantiates the necessity of a selective approach not only to territorial expansion, but also to the internal corporate processes when working out a development strategy. Based on the analysis of the specificity of products and their sales, the criteria for choosing areas for selective territorial expansion of the company are formulated. Taking into account certain criteria, based on the official statistics of the Republic of Kazakhstan, analytical Tables have been compiled reflecting the level of regional development by particular indicators. The analysis of the development of the territories of the Republic of Kazakhstan made it possible to rank the regions by the chosen criteria for selective territorial expansion, based on which the target regions were identified.